Cross-Cultural Education through Narratives: Promoting Tolerance, Identity, and Social Integration - Muhammad Rif’at; Ton Kiat; Nong Chai (Yayasan Adra Karima Hubbi, 2026)
Background. Cross-cultural education has become increasingly important in pluralistic societies where issues of tolerance, identity negotiation, and social integration shape educational priorities. Schools are expected to cultivate inclusive attitudes and intercultural competence; however, conventional approaches often emphasize factual cultural knowledge rather than transformative engagement. Purpose. This study aims to examine the effectiveness of narrative-centered instruction in promoting tolerance, strengthening identity awareness, and fostering social integration among secondary school students. The research investigates both cognitive and affective outcomes associated with structured engagement with culturally diverse stories. Method. A mixed-methods quasi-experimental design was employed involving 128 students divided into experimental and control groups. Quantitative data were collected using validated scales of tolerance, social integration, and identity awareness administered before and after an eight-week intervention. Qualitative data were obtained through reflective journals and classroom observations. Statistical analysis and thematic coding were conducted to triangulate findings. Results. Results indicate significant improvements in tolerance levels, inclusive identity formation, and peer interaction in the experimental group. Narrative engagement enhanced empathy and reduced stereotypical perceptions. Conclusion. The study concludes that cross-cultural education through narratives serves as an effective pedagogical strategy for promoting social cohesion and culturally responsive learning environments.